Surgical management of enchondroma with joint transfer: a case report - Banegas-Ruiz, Rodrigo; R., Baca-Domínguez C.; G., Campos-Angulo; I., Ríos de la Torre K.; Granados-Romero, Juan J.; Valderrama-Treviño, Alan I.; Mendoza-Barrera, German E.; Barrera-Mera, Baltazar (International Journal of Research in Medical Sciences, 2018)
The enchondromas are the most common benign bone tumor in the hands, mainly in young patients and its treatment is surgical in most cases due to its possible complications avoided through different procedures such as joint transfer, which allows to maintain a good quality of life for the patient. We present the case of a 42-year-old woman who came to the clinic for blunt trauma in the right hand where she was incidentally diagnosed with enchondroma on the third finger of the proximal interphalangeal joint of the right hand. Articular transfer of the proximal interphalangeal joint was performed. Second toe on the right, at 6 weeks corroborates correct evolution with bone consolidation of the articular transfer grade III and donor zone grade II, without infection complications, the correct recovery of the extensor movement range of this joint improving so their state of life should be the main objective of these procedures.